On the relationship between need for closure, stigmatising beliefs, and intention to seek psychological help - Loh, Siyuan (2019)
As part of a larger work on ‘Coping and Well-being’, the present study sought to elucidate the relationship between stigmatising beliefs of mental illness, Need for Closure (NFC), and intentions to seek psychological help (ISPH). First, I examined ‘weak-not-sick’ (WNS) beliefs of mental illness, asserting that holding these beliefs weaken ISPH. Next, I postulated that as compared to their low NFC counterparts, the epistemic proclivities of high NFC individuals would incline toward holding stronger ISPH. Finally, I contended that WNS beliefs compromise ISPH only if individuals agree with the content of such beliefs, and subsequently let them influence their beliefs about psychological help. Herein, I proposed that high NFC individuals would be more susceptible to the negative effects of WNS beliefs on ISPH; high NFC individual’s permanence tendencies predispose them to agree with prevailing beliefs of mental illness. As such, holding WNS beliefs would only be detrimental to high NFC individual’s ISPH, but not those low in NFC. As exploratory, I tested whether personal, and perceived WNS beliefs, would separately relate to ISPH, and if the proposed relationships vis-à-vis NFC and WNS beliefs would hold true for ISPH from informal sources of help-seeking. Although results failed to support the main hypotheses, they revealed a positive relationship between NFC and ISPH. This relationship remained even after controlling for the effects of personal, or perceived, WNS beliefs, suggesting that high NFC individuals hold stronger ISPH from their parents or close relatives than low NFC individuals when they experience mental health concerns. I discussed the implications of these findings and proposed suggestions for future research.